Understanding changes in teacher beliefs and identity formation: A case study of three novice teachers in Hong Kong. Issue 2 (3rd April 2021) - Huang, Jing; Wang, Yi; Teng, Feng
ABSTRACT: Novice teachers often undergo an identity shift from learner to teacher. Along this process, their instructional beliefs change considerably which in turn affect their teacher identity formation. Drawing on data collected mainly through interviews with three novice English teachers for more than one year, the present study examines their first-year teaching experience in Hong Kong secondary schools, focusing on changes of their English teaching beliefs and the impact of these changes on their identity construction. Findings reveal that while the teachers' initial teaching beliefs were largely shaped in their prior school learning and learning-to-teach experience, these beliefs changed and were reshaped a great deal when encountering various contextual realities, and these changes further influenced their views on their teacher identity establishment, unfortunately in a more negative than positive direction. The study sheds light on the importance of institutional support in affording opportunities for novice teachers' workplace learning and professional development.